ANALISIS PENGARUH KOMPETENSI, AKUNTABILITAS, INDEPENDENSI DAN PROFESIONALISME TERHADAP KUALITAS AUDIT DENGAN TEKANAN KLIEN SEBAGAI VARIABEL MODERATING - Susanto, Tomy (Jurusan Akuntansi FEB UNTAN, 2024)
The research aims to test the influence of competence, accountability, independence and professionalism on audit quality, as well as using client pressure moderation to test influences that strengthen independent variables against dependent variables. The data collection was done with a questionnaire, a likert scale of 1-5 through a google-form against the CAP in Jakarta as well as a physical questionnary against the auditors who work at the CAP Pontianak. Sampling method with simple random samples to give every auditor a chance to be a respondent, but with criteria as an auditor (junior auditor, senior auditor, dan partner). Data collection was carried out from 8 September 2023 to 8 October 2023 (1 month), with the results of 43 respondents from the Jakarta CAP but that could be used only 22 respondents. So the total sample used was 35 respondents from each auditor. The data analysis methods used in this study are double linear regression and moderated regression analysis (MRA) using SPSS v23 software. The results show that competence, independence and professionalism have a positive and significant impact on audit quality, while accountability has no impact on auditing quality.